Conjugation of a Hybrid Plasmid Encoding Hypervirulence and Carbapenem Resistance in Klebsiella pneumoniae of Sequence Type 592 - Zhao, Qian; Feng, Yu; Zong, Zhiyong (Frontiers in Microbiology, 2022)
Klebsiella pneumoniae simultaneously carrying genes encoding carbapenem resistance and hypervirulence causes fatal infections, representing a severe threat to human health. These carbapenem-resistant and hypervirulent K. pneumoniae (hvCRKP) strains are increasingly reported worldwide and have been found to belong to a variety of sequence types (STs). In this study, we report and characterized an hvCRKP strain of ST592, an uncommon ST, which caused a fatal infection in intensive care unit (ICU) in China and represents a novel type of hvCRKP. We demonstrated that this novel hvCRKP type emerged from the carbapenem-susceptible hypervirulent K. pneumoniae (hvKP) lineage of the K57 capsular type. K57 hvKP contains a pLVPK-like virulence plasmid and then acquired a conjugative blaKPC-2-carrying plasmid to form hvCRKP. The pLVPK-like virulence plasmid contains no complete conjugation module but was able to be transferred by fusion with the conjugative blaKPC-2-carrying plasmid during conjugation. This represents a new mechanism of simultaneous transfer genetic determinants of carbapenem resistance and virulence and highlights the undergoing expansion of hvCRKP, which requires rigorous monitoring and novel countermeasures to curb plasmid-mediated transmission.